Formation of Boron–Main-Group Element Bonds by Reactions with a Tricoordinate Organoboron L 2 PhB: (L = Oxazol-2-ylidene) - Kong, Lingbing (2017)
The reactivity of L2PhB: (1; L = oxazol-2-ylidene) as well as its transition-metal (chromium and iron) complexes toward main-group substrates have been systematically examined, which led to the construction of B–E (E = C, Ga, Cl, H, F, N) bonds. The combination of 1 and triethylborane smoothly captured carbon dioxide concomitant with the formation of B–C and B–O bonds. The soft basic boron center in 1 readily reacted with soft acidic gallium trichloride (GaCl3) to afford the extremely stable adduct 4 involving a B–Ga dative bond. Electrophilic alkylation of a neutral tricoordinate organoboron was first achieved by the treatment of 1 with dichloromethane and methyl trifluoromethanesulfonate (MeOTf), both of which afforded ionic species featuring an additional B–C bond. Comparatively, redox reactions took place when halides of heavier elements such as germanium dichloride, dichlorophenylphosphine, and chlorodiphenylbismuth were employed as substrates, from which cationic species 7 bearing a B–Cl bond was obtained. In addition, reactions of metal complexes [2, Cr(1)(CO)5; 8, Fe(1)(CO)4] with cationic electrophiles were investigated. With HOTf and FN(SO2Ph)2, the corresponding ionic species featuring a B–H bond (9) and a B–F bond (10) were formed via a formal electrophilic substitution reaction, whereas the reaction of 1 with F·Py-BF4 resulted in the formation of a dicationic boron species 11 with a newly formed B–N bond.